Structural heredity in the casting of eutectic cast iron - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2024)
It has been shown that the effect of structural inheritance in casting eutectic cast irons can be explained from the standpoint of nanostructured crystallization of foundry alloys. Proposed is a mechanism of structural heredity when casting eutectic cast irons. This mechanism is determined by the stability of the crystallization centers of microcrystals of austenite, graphite, cementite. This stability has been shown to depend on the concentration of adsorbed oxygen atoms. The higher this concentration, the less stable the centers of crystallization of microcrystals of austenite, graphite, cementite in melts of eutectic cast irons, and vice versa. With an increase in overheating and (or) the holding time of melts, the concentration of adsorbed oxygen atoms in them increases. As a result, structural stability during remelting of eutectic cast irons is reduced and the effect of structural heredity is disturbed.